RETRACTED: The Influence of Work Discipline, Work Motivation, and Organizational Commitment on The Performance of Employees of the DKI Jakarta Provincial Education Office - Mutiara Azzahra; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze the effect of work discipline, work motivation and organizational commitment on the performance of DKI Jakarta Provincial Education Office employees. The method of analysis in this study is descriptive analysis and inferential analysis. Data analysis through several tests, namely the research instrument test, classical assumption test, model feasibility test (F test), multiple linear analysis, and hypothesis testing (t test). The population in this study were permanent employees of the DKI Jakarta Provincial Education Office with a total of 150 employees, the number of samples in this study were 109 employees with data collection techniques through questionnaires. The results of the regression analysis in this study indicate that there is a positive and significant effect of work discipline, work motivation and work commitment on the performance of DKI Jakarta Provincial Education Office employees. The contribution of work discipline, work motivation, and organizational commitment affected the performance of DKI Jakarta Provincial Education Office employees, namely 0.638 or 63.8%, while the remaining 36.2% was explained by other variable factors that were not included in this study.